simplify 5a-8c+b+3c-9c+6b

1 answer

5a - 8c + b + 3c - 9c + 6b can be simplified by combining like terms:

Combining the terms with 'a': 5a

Combining the terms with 'b': b + 6b = 7b

Combining the terms with 'c': - 8c + 3c - 9c = -14c

Therefore, the simplified expression is:
5a + 7b - 14c
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions